PENERAPAN E-GOVERMENT BERBASIS WEB PADA BADAN PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK, KEPENDUDUKAN, ANAK DAN KELUARGA BERENCANA PROVINSI KALIMANTAN TENGAH - Widiatry, Widiatry; Sahay, Abertun Sagit; Ariska, Ria (Universitas Palangka Raya, 2015)
As with any application of electronic-government (e-government). E-government is one of the Government’s efforts in implementing the electronic-based governmental fields in improving the quality of public services effectively and efficiently. Viewed from the community needs to get good service then BP3AKKB Central Kalimantan Made the e-government services effectivelyand efficiently. Because it requires BP3AKKB E-Government so it can pass on information to the public about the implementation of activities as well as the public can pass on complaints acts of violence on women and children to the BP3AKKB.E-Government website was built using waterfall and web 2.0 technologies. Starting from the stage of the analysis is the stage design of use case diagrams, activity diagrams and class diagrams, peform a functional modeling analysis system by using UML. Next up is stage makingthe Coding System. In desingning and manufacturing use PHP, html, and java script. Xampp a web server, and MySQL as the database server. And the last stage of testing is in the form of with the method of blackbox.Web based e-government on womens empowerment And child protection, population, family planning and the province of Central Kalimantan it provide facilities to violence complaint contained features messages and notifications that are used as the interaction between society and the BP3AKKB. As well as training registation online.